Darolutamide antagonizes androgen signaling by blocking enhancer and super‐enhancer activation. Issue 9 (5th June 2020) - Baumgart, Simon J.; Nevedomskaya, Ekaterina; Lesche, Ralf; Newman, Richard; Mumberg, Dominik; Haendler, Bernard
Abstract : Prostate cancer (PCa) is one of the most frequent tumor types in the male Western population. Early‐stage PCa and late‐stage PCa are dependent on androgen signaling, and inhibitors of the androgen receptor (AR) axis represent the standard therapy. Here, we studied in detail the global impact of darolutamide, a newly approved AR antagonist, on the transcriptome and AR‐bound cistrome in two PCa cell models. Darolutamide strongly depleted the AR from gene regulatory regions and abolished AR‐driven transcriptional signaling. Enhancer activation was blocked at the chromatin level as evaluated by H3K27 acetylation (H3K27ac), H3K4 monomethylation (H3K4me1), and FOXA1, MED1, and BRD4 binding. We identified genomic regions with high affinities for the AR in androgen‐stimulated, but also in androgen‐depleted conditions. A similar AR affinity pattern was observed in healthy and PCa tissue samples. High FOXA1, BRD4, H3K27ac, and H3K4me1 levels were found to mark regions showing AR binding in the hormone‐depleted setting. Conversely, low FOXA1, BRD4, and H3K27ac levels were observed at regulatory sites that responded strongly to androgen stimulation, and AR interactions at these sites were blocked by darolutamide. Beside marked loss of AR occupancy, FOXA1 recruitment to chromatin was also clearly reduced after darolutamide treatment. We furthermore identified numerous androgen‐regulated super‐enhancers (SEs) that were associated with hallmark androgen and cell proliferation‐associated gene sets. Importantly, these SEs are also active in PCa tissues and sensitive to darolutamide treatment in our models. Our findings demonstrate that darolutamide is a potent AR antagonist blocking genome‐wide AR enhancer and SE activation, and downstream transcription. We also show the existence of a dynamic AR cistrome that depends on the androgen levels and on high AR affinity regions present in PCa cell lines and also in tissue samples. Abstract : Schematic model showing how darolutamide blocks androgen (R1881)‐mediated AR signaling by inhibiting the function of normal enhancers and super‐enhancers, and impairing downstream gene transcription.